Once upon a time there was a world, but poetry killed it: Maillard's position on the poetic and poetry in perspective (2022)
Chantal Maillard has been one of the most relevant thinkers of recent years. Her creative and bold approach has explored one of the most important tensions in today’s culture: that which results from the encounters and conflicts between philosophy and poetry. Starting from a Maillardian perspective, this article addresses the place of the poetic in today’s world. To this end, I argue that the distinction between poetry and poem is one of the central hypotheses of Maillard’s proposal. And this distinction allows us to understand that the poetic is part of the existential flux by which a specific phenomenon of the world can end and give rise to another, in response to the dissatisfactions that feed the desire for something other than what is already there, and that it is a response to the dissatisfactions that nourish the desire for something other than what is already there.